2013
DOI: 10.2147/copd.s40885
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental vitamin D and physical performance in COPD: a pilot randomized trial

Abstract: BackgroundLow 25-hydroxyvitamin D (25[OH]D) levels, commonly observed in chronic obstructive pulmonary disease (COPD), are associated with muscle weakness in elderly populations, and vitamin D supplementation appears to improve muscle strength and decrease falls in older individuals. We tested the effect of vitamin D supplementation on physical performance in patients with COPD.MethodsPatients were randomized to daily cholecalciferol (2000 IU) or placebo for 6 weeks. The primary outcome was the 6-week change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
3
13
2
Order By: Relevance
“…Given that serum 25(OH)D deficiency was mainly observed in severe COPD patients, the protective effects of 25(OH)D in severe COPD patients was compared with that in mild COPD patients. While our results are not consistent with the study conducted by Bjerk et al 40 our conclusion was not influenced. First, a limited number of patients (n=36) were included in that study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Given that serum 25(OH)D deficiency was mainly observed in severe COPD patients, the protective effects of 25(OH)D in severe COPD patients was compared with that in mild COPD patients. While our results are not consistent with the study conducted by Bjerk et al 40 our conclusion was not influenced. First, a limited number of patients (n=36) were included in that study.…”
Section: Discussioncontrasting
confidence: 99%
“… 9 , 38 Only the study conducted by Bjerk et al reported that there was no obvious benefit for severe COPD patients with vitamin D supplement based on two questionnaire scores (Short Physical Performance Battery and St George’s Respiratory Questionnaire). 40 Generally, vitamin D intake was a safe approach without severe side effects for COPD patients based on most studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have been performed assessing the effect of vitamin D supplementation on physical performance in patients with COPD. A pilot RCT did not show effects of vitamin D supplementation on physical performance, but was limited by the small number of 36 participants and short follow-up of 6 weeks [ 32 ]. Also, the study was not specifically aimed at patients with vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Vitamin D supplementation has also been suggested for improving physical performance, but a recent randomised trial did not show any benefits in this regard. [26] Although vitamin D deficiency may contribute to morbidity in COPD patients, a lack of vitamin D does not appear to contribute to excess mortality. [27] …”
Section: Asthma and Vitamin D Levelsmentioning
confidence: 99%